Building Legal Awareness and Democracy: Revitalizing the Role of Citizenship Education for Students of SMAN 7 Kediri City - Sutiyono (Fakultas Hukum Universitas Kadiri, 2021)
ABSTRACTRecently, a lot of students have participated in demonstrating againstgovernment policies. Even though, they do not know the detailed contents of thegovernment policies they are about. In fact, in practicing democracy, it is notuncommon for them to violate the law by committing acts of anarchy, destroyingpublic facilities, and other acts of fandalism. The purpose of this research is todescribe qualitatively about the role of Citizenship Education in increasing legalawareness and awareness of democracy. The method used is descriptive qualitative.The research was conducted At the SMAN 7 Kediri Kediri City. The researchsubjects were school principals, students, Civics teachers and Guidance andCounseling Teachers. Data were collected using participatory observation methodsand in-depth interviews. Data relating to documents owned by the school werecollected using the library documentation method. The data that has been collectedis analyzed using methods of: 1) data collection, 2) data classification, 3) datafiltering, and 4) drawing conclusions. To improve the accuracy and consistency ofthe data, triangulation methods in the form of snowballing were used, prolongedstay at the research location, and made temporary conclusions until data saturationwas reached. The results showed that, Citizenship Education was able to increaselegal awareness and was able to increase democratic awareness among students ofSMAN 7 Kota Kediri.Keywords : Education, citizenship, law, democracy, students